INTERNALIZATION OF ISLAMIC EDUCATIONAL VALUES IN SIRANGKAP QUR'ANIC VILLAGE: A CASE STUDY - Wulandari, Martina Ayu; Maimun, Agus; Kawakip, Akhmad Nurul (Edukasi Islami: Jurnal Pendidikan Islam, 2025)
Background: This study is grounded in the importance of Islamic education in shaping community character and the need to understand how Qur’anic values are internalized within a religious community that consistently upholds them in daily life. Purpose: The research aims to analyze the process of internalizing Islamic educational values in the Qur’anic Village of Sirangkap, Mandailing Natal, through five interconnected stages: value transformation, value transaction, transinternalization, social integration of values, and value formalization. Method: Employing a qualitative phenomenological approach, data were collected through in-depth interviews, participant observation, and document analysis, and examined using Muhaimin’s theory of value internalization, Bandura’s social learning theory, Piaget–Kohlberg’s moral development theory, Vygotsky’s sociocultural theory, and Durkheim’s concept of social integration. Result: The findings reveal that Islamic values are internalized through five interconnected stages: value transformation, value transaction, transinternalization, social integration, and value formalization. This process is sustained through parental and religious role modeling, educational interactions in schools and community spaces, collective religious habituation, strong social cohesion based on ukhuwah, and the institutionalization of values within village regulations and religious institutions. As a result, Islamic values evolve from external norms into intrinsic motivations that shape individual behavior and collective identity. Conclusion: This study demonstrates that the Sirangkap model offers a sustainable community-based framework for Islamic value education, which can inform similar initiatives in other rural or socially vulnerable communities seeking to strengthen moral character and social resilience through Islamic education.